The Boltzmann project. (5th February 2018) - Fischer, J; Fellmuth, B; Gaiser, C; Zandt, T; Pitre, L; Sparasci, F; Plimmer, M D; de Podesta, M; Underwood, R; Sutton, G; Machin, G; Gavioso, R M; et al.
Abstract: The International Committee for Weights and Measures (CIPM), at its meeting in October 2017, followed the recommendation of the Consultative Committee for Units (CCU) on the redefinition of the kilogram, ampere, kelvin and mole. For the redefinition of the kelvin, the Boltzmann constant will be fixed with the numerical value 1.380 649 × 10 −23 J K −1 . The relative standard uncertainty to be transferred to the thermodynamic temperature value of the triple point of water will be 3.7 × 10 −7, corresponding to an uncertainty in temperature of 0.10 mK, sufficiently low for all practical purposes. With the redefinition of the kelvin, the broad research activities of the temperature community on the determination of the Boltzmann constant have been very successfully completed. In the following, a review of the determinations of the Boltzmann constant k, important for the new definition of the kelvin and performed in the last decade, is given.